Stereotip Pekerjaan Berbasis Gender Dalam Konteks Indonesia - Kinanti, Nur Alifta; Syaebani, Muhammad Irfan; Primadini, Dindha Vitri (UI Scholars Hub, 2021)
There is a stereotype about masculine and feminine occupation in the society. This occupational gender stereotype will lead to several negative impact, it could make someone who do the occupa- tion that is contrary to his gender identity to experience an identity crisis and tend to deviate. This study aims to determine the classification of masculine and feminine occupations and the underly- ing reason behind the classification. Data were collected by distributing questionnaires filled out by 3.633 respondents aged 15-64 years and from all over Indonesia. The analysis was carried out using quantitative methods with the help of SPSS 22 and Microsoft Excel software. From the results of the analysis, it was found that there were 46 masculine jobs, 57 neutral jobs, and 26 feminine jobs. In addition, the number of sexes doing work is the strongest basis for a person to classify an occupation as a masculine or a feminine occupation. For academician and businessman the results of this study are expected to provide the insight into the classification of gender-based stereotype of occupations especially in Indonesia. As for industry, the results of this research can become the basis for creating human resource policies that are gender responsive.